Mechanical and Durability Characteristics of Roller Compacted Geopolymer Concrete Using Reclaimed Asphalt Pavement - Rahman, Sk Syfur; Khattak, Mohammad Jamal (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Every year a large quantity of reclaimed asphalt pavement (RAP) is generated in the USA. Utilization of RAP can solve the storage problem, prevent environmental pollution and reduce construction costs. This study focuses on the strength and durability characteristics of RAP mixtures by introducing the concept of roller-compacted fly ash-based geopolymer concrete (RCGPC). Several selected RCGPC mixtures were investigated to evaluate the effect of mixture variables, including sodium hydroxide (NaOH) molarity, sodium silicate (Na2SiO3) to sodium hydroxide (NaOH) ratio on the strength, modulus and durability characteristics of the mixtures. The effects of different curing temperature and curing duration on compressive strength were also studied. It was found that the mixtures with Na2SiO3/NaOH ratio of 1 yielded about 12 % higher compressive strength than the ratio of 0. Further, the mixtures using 10M NaOH and alkali ratio of 1 produced about 25% higher compressive strength than 8M NaOH which produced about 17 MPa. Similar results were obtained for elastic modulus and split tensile strength of the mixtures. Freeze-thaw durability tests also revealed acceptable results for the RCGPC mixtures. Formation of new geopolymeric compounds and chemical bonds in the newly formed novel RCGPC mixtures were also discovered using XRD analysis. The comparison of mechanical and durability testing further showed that RCGPC performed better than the roller-compacted cement concrete (RCC) using RAP. Based on the results and analysis the developed RCGPC using RAP could be used as a cost-effective solution for the construction of pavement structures.